2015
DOI: 10.1039/c4ra14938f
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-ultrasound simultaneous irradiation: a hybrid technology applied to ring closing metathesis

Abstract: A new hybrid microwave (MW) and ultrasound (US)-assisted reactor concept was investigated. The 2.45 GHz microwaves were delivered with a semiconductor generator via a coaxial cable to a monomode Transverse Electric (TE) microwave resonant cavity within which the reactor was placed; the US (25 kHz) were delivered at the bottom of the TE cavity via a novel designed sonotrode consisting of a detacheable metallic plate-probe (indirect sonication). The semiconductor microwave generator helped to optimize the absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…However, the use of microwave or ultrasound irradiation promoted the undesired isomerisation of the C=C bond, thus lowering the yields of the desired product 9 (Table 1, entries 3 and 4). This result is in agreement with the known fact that in protic solvents ruthenium hydrides are formed leading to isomerisation byproducts [66]. Finally, we were pleased to see that the use of ultrasound or microwave irradiation were beneficial for the CM of alcohol 8 with methyl acrylate ( 10 , Table 1, entries 5 and 6) resulting not only in increased conversion but also reducing the amount of the unwanted product of self-metathesis of 8 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, the use of microwave or ultrasound irradiation promoted the undesired isomerisation of the C=C bond, thus lowering the yields of the desired product 9 (Table 1, entries 3 and 4). This result is in agreement with the known fact that in protic solvents ruthenium hydrides are formed leading to isomerisation byproducts [66]. Finally, we were pleased to see that the use of ultrasound or microwave irradiation were beneficial for the CM of alcohol 8 with methyl acrylate ( 10 , Table 1, entries 5 and 6) resulting not only in increased conversion but also reducing the amount of the unwanted product of self-metathesis of 8 .…”
Section: Resultssupporting
confidence: 86%
“…Both methods were shown in the past to be responsible for shortening the reaction time, increasing the reaction yield or even favour the formation of the desired product when compared to traditional protocols [5657]. In the case of olefin metathesis, examples of application of those techniques are well documented for organic solvents [5866], surprisingly, examples describing reactions in aqueous media are scarce and thus merit further investigation [6768].…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that this was due to molecular interactions between the ruthenium-based carbene complex and oleic acid, and concluded that some catalyst may have stuck to the wall of the reaction vial, thus limiting reaction yields. An ultrasound probe was used to ensure effective mixing (Gulajski et al, 2008;Jakobs and Sijbesma, 2012;Piermattei et al, 2009;Sacco et al, 2015;Sari et al, 2013). With sonication and in the absence of solvent, higher rates of oleic acid conversion were observed after only 5 h of reaction (Tab.…”
Section: Schemamentioning
confidence: 99%
“…After 2010 a number of papers were published having as topic either two steps processes, like metal organic framework IRMOF-1 synthesis [12], (in a separate reactors as stated by Lionelli and Mason), synthesis of polysubstituted pyridines under combined microwave and ultrasound irradiation [13], porous manganese dioxide (MnO2) synthesized via an ultrasound-microwave-intensified precipitation [14] (perhaps in a single reactorthe papers do not offers details of equipment), or even for biodiesel preparation emphasizing the synergetic effects of combining both source of energy in one device [15]. Several papers shown how to build or review the simultaneous ultrasound and microwave new reactor [16][17][18][19], others how to use this combination for adding value to some byproducts (like glycerol from biodiesel synthesis) [20]. Clearly there are efforts in developing such a combined device in which MW and US could be used together in a controllable mode.…”
Section: Introductionmentioning
confidence: 99%
“…This device is produced by SAIREM and is described in a paper published few years ago by Sacco et. al., [17] as a hybrid technology applicable for a specific process (ring closing metathesis) and is in use in our laboratory from a couple of years. This device is having as ultrasonic source a modified ultrasonic cleaning bath to be attachable to the MW unit (see figure 5).…”
Section: Introductionmentioning
confidence: 99%